Edited 1H magnetic resonance spectroscopy in vivo: Methods and metabolites. Issue 4 (2nd February 2017) - Harris, Ashley D.; Saleh, Muhammad G.; Edden, Richard A.E.
Abstract : The Proton magnetic resonance ( 1 H‐MRS) spectrum contains information about the concentration of tissue metabolites within a predefined region of interest (a voxel). The conventional spectrum in some cases obscures information about less abundant metabolites due to limited separation and complex splitting of the metabolite peaks. One method to detect these metabolites is to reduce the complexity of the spectrum using editing. This review provides an overview of the one‐dimensional editing methods available to interrogate these obscured metabolite peaks. These methods include sequence optimizations, echo‐time averaging, J ‐difference editing methods (single BASING, dual BASING, and MEGA‐PRESS), constant‐time PRESS, and multiple quantum filtering. It then provides an overview of the brain metabolites whose detection can benefit from one or more of these editing approaches, including ascorbic acid, γ‐aminobutyric acid, lactate, aspartate, N‐acetyl aspartyl glutamate, 2‐hydroxyglutarate, glutathione, glutamate, glycine, and serine.Magn Reson Med 77:1377–1389, 2017. © 2017 International Society for Magnetic Resonance in Medicine.